Performance assessment of OpenFOAM and FLOW-3D in the numerical modeling of a low Reynolds number hydraulic jump. (June 2016) - Bayon, Arnau; Valero, Daniel; García-Bartual, Rafael; Vallés-Morán, Francisco ​José; López-Jiménez, P. Amparo
Abstract: A comparative performance analysis of the CFD platforms OpenFOAM and FLOW-3D is presented, focusing on a 3D swirling turbulent flow: a steady hydraulic jump at low Reynolds number. Turbulence is treated using RANS approach RNG k- ε . A Volume Of Fluid (VOF) method is used to track the air–water interface, consequently aeration is modeled using an Eulerian–Eulerian approach. Structured meshes of cubic elements are used to discretize the channel geometry. The numerical model accuracy is assessed comparing representative hydraulic jump variables (sequent depth ratio, roller length, mean velocity profiles, velocity decay or free surface profile) to experimental data. The model results are also compared to previous studies to broaden the result validation. Both codes reproduced the phenomenon under study concurring with experimental data, although special care must be taken when swirling flows occur. Both models can be used to reproduce the hydraulic performance of energy dissipation structures at low Reynolds numbers. Highlights: Two CFD models: OpenFOAM and FLOW-3D for hydraulic jump in low Reynolds numbers. Representative variables are compared for the two CFD results and experimental data. The model results are also compared to previous studies with good agreement. Both CFD codes had good behavior, but special care is required with swirling flows. A quantification of both models accuracy relating to studied variables is proposed.